Sistema desequilibrado: uma análise crítica das justificativas filosóficas para a lei de direitos autorais através da lente dos direitos dos usuários - Longan, Mitchell (Unisanta Law and Social Science, 2025)
New technology and the internet have fundamentally changed the way many ordinary people approach creative works. We are no longer simply consumers of content. Instead, many of us now want to interact with the content we love, reshape it and put it back into the world. This practice can take many forms such as fan fiction, remixed music, videogame livestreams, fan films, and even internet memes. However, while we as a society are gradually following a trajectory that appears to be more and more liberal with notions of copyright and ownership over creative expression, the law is not following that same trajectory. In fact, the law has grown more and more restrictive over the last century with respect to this sort of expression. This presentation is about the rights of users, the ordinary people who use the copyrighted content they love in the creation of new expressive works- those who use content rather than simply consume it. Ultimately, it has three goals. The first is to offer an analysis of users’ rights under copyright law from four commonly used theoretical perspectives. These are labor, personality, economic and utilitarian theories. In doing so, it will demonstrate that the philosophies that underpin modern copyright law support a broad and liberal set of rights for derivative creativity. It will argue that current treatment of derivative works is unnecessarily conservative from a theoretical perspective. Second, this presentation will demonstrate how, in spite of theory that supports a healthy community of derivative creativity, those who practice it have been further disenfranchised by the law. Using U.S. law as a case study, I will argue term limit extensions, increased protectionist treatment of secondary works online, and the functional lack of access to proper licensing mechanisms have rendered users’ rights impotent. Finally, in conclusion, I will offer a solution to the apparent imbalance of power in the form of replacing property-based derivative rights with liability rules.